[József Khogler 5]
aunty around the house, children&parents, chicken, a girl carrying one of them, pig working up in snow-covered yard, "House-competition" shooted by Jenő Khogler making hair-cut and showing hair-styles, giving prizes, 1970 May Day, procession, brass-band, foreign students, flags & transparents, politicians on the grandstand,